Tunable resonant Bragg photonic bandgap structures based on active quantum dot layers; crystals with applications in all-optical switches manufacturing. Issue 2 (4th March 2022) - Roshan Entezar, Samad; Ghasemi, Fatemeh; Razi, Sepehr
Abstract : Novel tunable photonic bandgap structures are proposed in this paper. Alternately placed slabs of GaAs (as barriers) and layers containing InAs/InGaAs quantum dots (active dipole elements) are considered as the main building blocks of the proposed crystals. The common transfer matrix method is utilized for characterization of the optical features of the structures. However, to take more physical phenomena into considerations, effective excitonic susceptibility is defined in a way that includes all the homogeneous and non-homogeneous broadenings. Dependences of the optical responses to the structural parameters such as the number of periods, uniformity of the quantum dots, and the size of the barrier/dots are investigated at the first step. Extracting the optimum values, tunability of the optical features of the structures by changing the crystal temperature, light incident angle and also illuminating an external pump laser is investigated then. To study the potential of the proposed structures to be used as all-optical switches, the response of the crystals to the square wave pulse series of 50 ps duration and data sequences of 10101 is studied by turning the pump pulse on and off. Results are notable for less quantum dot size fluctuations and low temperatures.